THE RESULTS OF COMPUTER MORPHOMETRY USED IN ENDOMETRIAL HYPERPLASIA - Yu. Yu. Tabakman; I. B. Manukhin; A. G. Solopova; A. A. Kanibolotsky; A. Kh. Bishtavi; O. A. Gornykh; V. V. Samoylenko; V. N. Gulieva; Kh. T. Gogoladze; N. G. Chikovani (Акушерство, гинекология и репродукция, 2016)
Differencial diagnostics of simple, complex and atypical hyperplasia and endometrial cancer(SEH, CEH, AEH, EC) presents a number of difficulties which often lead to a different interpretation of the same histologic samples. Theaim: to evaluate the ability of computer morphometry(CM) used in case of endometrial hyperplasia. Material: 36 patients, including 12 patients with SEH, 11 patients with CEH, 7 patients with AEH and 5 patients with EC. Method of ImaScopeColor morphometric programme. Conclusion: morphometric changes that occur in case of endometrial hyperplasia expressed in quantitative terms are more varied than their schematic definition in modern classification which in its turn may be the cause of the discrepanies in diagnoses.